Analisis Biaya Dinding Plesteran Acian Vs Dinding Bata Ekspos Sederhana (Studi Kasus: Kota Palopo) - Intang Intang; Anggel Erpa Erong Pakiding (CV. SINAR HOWUHOWU, 2026)
Research on wall construction cost comparisons in Palopo City concludes that using simple exposed brick walls is much more economical and efficient than conventional plastering and skimming methods. Based on unit price analysis, the total cost for conventional wall construction requires an expenditure of Rp249,380.32 per m2. In contrast, the simple exposed brick method, which relies only on quality red bricks, neat joint finishing, and a transparent anti-moss coating, costs only Rp170,250.00 per m2. Although the material price for red bricks specifically chosen for the exposed method is slightly higher at the initial purchase, this approach proves capable of cutting the budget by up to 31.73%, saving approximately Rp79,130.32 per m2. This major saving occurs because the method completely eliminates the need for cement and sand materials for both plastering and skimming. Aside from financial advantages, eliminating the plastering and skimming stages also directly impacts the efficiency of worker duration in the field. This reduced construction time automatically lowers labor wage costs due to a drop in the man-hours index. Technically, applying simple exposed brick is not only effective in cutting construction budgets, but also accelerates the overall project completion schedule. This concept holds strong potential to serve as an alternative standard for residential or commercial building construction featuring an industrial-minimalist style in Palopo City, providing a solution that is economical, fast, and high in aesthetic value.